REKONSTRUKSI TUJUAN PENDIDIKAN ISLAM - Muhamad Fajri; Khojir Khojir (Universitas Islam Negeri Sumatera Utara Medan, 2022)
This study aims to identify and analyze human nature from an Islamic perspective and then formulate the formulation of Islamic education goals based on that human nature. This research is a library research, using content analysis and with a philosophical approach. The source of data in this study is in the form of the Qur'anic text, and statements of experts which are also in the form of text, including texts in the form of books, as well as relevant research as data in this study. The results show that related to the nature of humans whose creation was to worship Allah and were given the mandate to manage the universe or the caliph fil ardh, so to meet these duties and responsibilities, the purpose of Islamic education is directed at increasing monotheism, justice for others, sincerity in life, a high sense of responsibility and always do good deeds.